Supervision during strength training-the interplay with facilitation, feedback and attentional focus: a narrative review - Fisher, J. P. (Sports Medicine, 2025)
There is a growing body of research supporting the acute and chronic benefits of supervision during strength training. However, to date, there has been a lack of clarity within the terminology used, as well as when considering the differences between supervision and facilitation, and connections between supervision, feedback and attentional focus. Multiple articles have identified a lack of transparency in previous research and a need for greater detail on key elements which form the basis of supervision. The aim of this review is to discuss supervision as a construct within the parameters of strength training, including differentiating characteristics along a spectrum from supervision to facilitation, the use of different mediums (one-to-one, small group and virtual) and the effects of internal feedback (including perceptions and measures of effort), external feedback (including contemporary technological approaches) and attentional focus, and augmented feedback upon performance outcome measures. Finally, this review discusses the possible importance of positive feedback within supervision and the position of personal training and strength coaching as a service industry, as well as providing context around autonomy and input on the part of the trainee. In context, this paper provides guidance for future researchers about presenting clarity and detail of supervision and feedback, while also providing practitioners with information to stimulate awareness in coaching practices.